2015
DOI: 10.1016/j.vaccine.2015.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Three randomized trials of maternal influenza immunization in Mali, Nepal, and South Africa: Methods and expectations

Abstract: Influenza infection in pregnancy can have adverse impacts on maternal, fetal, and infant outcomes. Influenza vaccination in pregnancy is an appealing strategy to protect pregnant women and their infants. The Bill & Melinda Gates Foundation is supporting three large, randomized trials in Nepal, Mali, and South Africa evaluating the efficacy and safety of maternal immunization to prevent influenza disease in pregnant women and their infants <6 months of age. Results from these individual studies are expected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 31 publications
0
42
0
2
Order By: Relevance
“…We determined an assumed baseline rate for PTB, SGA, and LBW outcomes based on three sources of information from three regions in the world using PubMed and study reports. [16][17][18][19] Sensitivity analyses were performed, including all published studies irrespective of sample size. The main analyses only included observational studies, in separate sensitivity analyses, the RCTs were also included.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We determined an assumed baseline rate for PTB, SGA, and LBW outcomes based on three sources of information from three regions in the world using PubMed and study reports. [16][17][18][19] Sensitivity analyses were performed, including all published studies irrespective of sample size. The main analyses only included observational studies, in separate sensitivity analyses, the RCTs were also included.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A number of studies have reviewed the impact of this change in policy, with studies from the UK [25] and USA [26] indicating that the strategy appears to be safe and effective, although a very recent study has highlighted the impact of maternal immunisation on the response to postnatal pertussis immunisation and other vaccines in the routine immunisation programme that are conjugated to the diphtheria toxin variant [27]. Other groups report a reduction of morbidity in the mothers and their infants when mothers are immunised with influenza vaccine during pregnancy [28]. The effect is not as great as that observed with pertussis and the authors do note the challenges in interpreting the data and providing recommendations, given seasonal and year-to-year variations in disease severity and incidence.…”
Section: Maternal Immunisationmentioning
confidence: 99%
“…In Nepal, yearround maternal influenza immunization significantly reduced maternal influenza-like illness, influenza in infants and low birth weight, suggesting that this strategy could be useful in subtropical regions where influenza is present for many months [61]. Regarding safety, IIV did not increase risk of foetal death, spontaneous abortion or congenital malformations [59][60][61][62].…”
Section: Influenzamentioning
confidence: 92%
“…Results from a randomized controlled trial in Bangladesh provided a proof of concept that maternal vaccination could reduce infant influenza disease in developing countries, with 36% efficacy against febrile respiratory illness in mothers and 29% in infants and 63% efficacy against confirmed influenza illness in infants, compared to the 23-valent pneumococcal polysaccharide vaccine [58]. Three large, controlled, randomized trials in Nepal, Mali and South Africa then evaluated the efficacy and safety of maternal immunization to prevent influenza disease in pregnant women and their infants aged <6 months [59]. In the South African placebo-controlled trial, vaccine efficacy against confirmed influenza was approximately 50% both in mothers and infants [60].…”
Section: Influenzamentioning
confidence: 99%